The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jfmm-05-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and obstacles for fashion renting: a cross-cultural comparison

Abstract: Purpose The purpose of this paper is to identify the influences of perceived enjoyment, perceived risks and attitude on the intention to rent fashion products for both Chinese and American consumers. Furthermore, this study is expected to empirically identify the differences between American and Chinese consumers in terms of motivations for and barriers to fashion renting. Design/methodology/approach Data were collected through online surveys in both the USA and China. Data cleaning generated 412 usable samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 40 publications
(42 reference statements)
3
66
0
Order By: Relevance
“… Benoit, Baker, Bolton, Gruber, and Kandampully (2017) suggested that consumers may find hedonic value by using otherwise unaffordable items. Indeed, enjoyment is one of the strongest contributors to attitudes toward CC in general ( Hamari et al, 2016 ) as well as to domain-specific attitudes toward fashion rental ( Lang et al, 2019 ). Enjoyment is known as a strong driver of consumers’ participation in CC, particularly clothing consumption ( Becker-Leifhold & Iran, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Benoit, Baker, Bolton, Gruber, and Kandampully (2017) suggested that consumers may find hedonic value by using otherwise unaffordable items. Indeed, enjoyment is one of the strongest contributors to attitudes toward CC in general ( Hamari et al, 2016 ) as well as to domain-specific attitudes toward fashion rental ( Lang et al, 2019 ). Enjoyment is known as a strong driver of consumers’ participation in CC, particularly clothing consumption ( Becker-Leifhold & Iran, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enjoyment is known as a strong driver of consumers’ participation in CC, particularly clothing consumption ( Becker-Leifhold & Iran, 2018 ). This is because consumers find the process of renting as a way of treasure hunting that offers the greatest fulfillment and desired outcome at the lowest cost ( Lang et al, 2019 ). In this process, consumers enjoy not only the outcomes of renting but also the process as “a playable activity” to build their own infinite closet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, consumers express a desire to take advantage of a variety of items and models, placing increased attention on sustainability and affordability of sources. More and more consumers prefer to rent clothes rather than buy them [28,29].…”
Section: Introductionmentioning
confidence: 99%